PARADIGMA KAJIAN DAN PENGAJARAN FILOSOFIS, HOLISTIK, DAN INTEGRATIF SAINS EKSAKTA DI TADRIS IPA BIOLOGI UIN MATARAM - Lestari Lestari; Ervina Titi Jayanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
The main purpose of Indonesian national education system is to create a Pancasilais human being, characterized by living with religious values and noble humanity. Islamic higher education then played a significant role by developing an education system that integrated science and religion into their curriculum by put some specific Islamic theology course/subject onto their science department. In consequence, the paradigm learning model which is phylosophicaly, holistic, and integrative is strongly needed. This kind of learning model would give birth to an aksiological aspect by emerging the spiritual factor. Thereby, religion would became a value system that always embedded in every science course/subject.